Stepwise Versus Concerted Mechanisms in General‐Base Catalysis by Serine Proteases. (21st December 2015) - Uritsky, Neta; Shokhen, Michael; Albeck, Amnon
Abstract: General‐base catalysis in serine proteases still poses mechanistic challenges despite decades of research. Whether proton transfer from the catalytic Ser to His and nucleophilic attack on the substrate are concerted or stepwise is still under debate, even for the classical Asp‐His‐Ser catalytic triad. To address these key catalytic steps, the transformation of the Michaelis complex to tetrahedral complex in the covalent inhibition of two prototype serine proteases was studied: chymotrypsin (with the catalytic triad) inhibition by a peptidyl trifluoromethane and GlpG rhomboid (with Ser‐His dyad) inhibition by an isocoumarin derivative. The sampled MD trajectories of averaged p K a  values of catalytic residues were QM calculated by the MD‐QM/SCRF(VS) method on molecular clusters simulating the active site. Differences between concerted and stepwise mechanisms are controlled by the dynamically changing p K a  values of the catalytic residues as a function of their progressively reduced water exposure, caused by the incoming ligand.